2015
DOI: 10.1177/0885328215617327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug release from poly(lactide-co-glycolide) microspheres and novel fibre formulations

Abstract: Intraperitoneal cisplatin delivery has recently been shown to benefit ovarian cancer patients. Cisplatin-containing poly(lactide-co-glycolide) (PLGA) microspheres have been proposed for cisplatin delivery. The drug loading of cisplatin containing microspheres produced elsewhere is 3-10%w. Similar microspheres are reported here with a mean diameter of 38.8 µm, and a drug loading of 11.7%w, but using ethyl acetate as a safer solvent. In addition, novel formulations of cisplatin-containing solid and hollow PLGA 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
1
7
2
Order By: Relevance
“…For simulations corresponding to the Release Module, the transport parameters used to fit the model are presented in Table . The estimated value of the drug effective diffusivity was 2 × 10 −14 cm 2 s −1 , which is in agreement with those reported for drugs of similar physicochemical characteristics (molar mass and water solubility) in PLGA microspheres under similar conditions …”
Section: Resultssupporting
confidence: 90%
“…For simulations corresponding to the Release Module, the transport parameters used to fit the model are presented in Table . The estimated value of the drug effective diffusivity was 2 × 10 −14 cm 2 s −1 , which is in agreement with those reported for drugs of similar physicochemical characteristics (molar mass and water solubility) in PLGA microspheres under similar conditions …”
Section: Resultssupporting
confidence: 90%
“…Our diffusion results are higher than Campbell et al () who observed much slower cisplatin diffusivity from PLGA microspheres. Campbell's lower diffusivity of cisplatin was caused by the low molecular mobility of the matrices where cisplatin is encapsulated.…”
Section: Resultscontrasting
confidence: 83%
“…Our results are compared to the in vitro release of cisplatin from core‐shell poly(lactide‐ co ‐glycolide) (PLGA) nanoparticles (Reardon et al, ), PLGA microspheres, solid fibers, and hollow fibers (Campbell et al, ), and electrostatically cross‐linked chitosan‐alginate nanoparticles (Maan et al, )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations